MiRNA-23a-5p is the biomarkers for gouty arthritis and promotes inflammation in rats of gouty arthritis via MyD88/NF-κB pathway by induction TLR2 - Fang Li; Jian-Hua Yao; Li Li; Qian Nie; Jing-Jing Cao; Xiao-Ran Ning (Archives of Rheumatology, 2022)
Objectives: In this study, we aimed to examine the efficacy of micro ribonucleic acid (miRNA)-23a-5p in gouty arthritis and to investigate its possible mechanism. Materials and methods: Gouty arthritis in rat was established by intraarticular injection of 0.2 mL monosodium urate crystal (20 mg/mL) inside knee joint cavity. THP-1 cell was induced using lipopolysaccharides (LPS) for in vitro model. Results: Serum miRNA-23a-5p expression levels were increased in rats of gouty arthritis. However, overexpression of miRNA-23a-5p promoted inflammation and induced myeloid differential protein-88 (MyD88)/nuclear factor-kappa B (NF-κB) pathway by induction toll-like receptor-2 (TLR2) in vitro. The inhibition of TLR2 attenuated the pro-inflammation effects of miRNA-23a-5p in inflammation in in vitro model of gouty arthritis. Conclusion: Our findings demonstrate that miRNA-23a-5p is a biomarker for gouty arthritis and promotes inflammation in rats of gouty arthritis via MyD88/NF-κB pathway by targeting TLR2.